Investigating the perception of perfusion educators on the training programmes in cardiovascular perfusion in South Africa - Ali-Musa, Zainul Abideen (SA Heart Journal, 2018)
Background: Perfusion education and training varies considerably throughout the world. In South Africa, only 3 universities offer the Bachelor of Technology degree in clinical perfusion. But, unlike most developed nations, where a common curriculum for perfusion education has been established, perfusion education in South Africa is plagued by the lack of standardised training curriculum, study and exit-level outcomes and competencies required of a cardiovascular perfusionist. Hence, this study aims to investigate the perception of perfusion educators on the adequacy and validity of current training programmes in cardiovascular perfusion in South Africa with a view to develop a standardised curriculum for perfusion education. Methods: A descriptive, exploratory study design which employed a quantitative methodology using a questionnaire survey was used to obtain both qualitative and quantitative data on the perception of perfusion educators on the adequacy and validity of current training programmes in cardiovascular perfusion in South Africa. Results: This study recorded a response rate of 71.4%. Perfusion educators in South Africa are in agreement that there is a need for a standardised curriculum and that a single exit examination, in both oral and written formats, conducted by a regulatory body, should be a requirement for certification and registration. Conclusion: This study highlights the need for a revised, standardised curriculum for perfusion education in South Africa in order to improve competency amongst perfusion graduates and to produce perfusionists who are able to successfully apply their knowledge and skills to improve patients’ outcome.